Impact of Rhizobacterial Strains on Soil Physicochemical Properties and Wheat (Triticum Aestivum L.) Productivity - Khan, Rashid; Yasar Saleem Ahmed Khan; Tahir Yab Khan; Sania Ijaz; Mohammad Ashfaq; Hassan, Arbaz; Alam, Hafiz Munsif; Ahmad, Tariq; Iram, Munaza; Javed, Hina (Journal of Agriculture and Biology, 2025)
A field experiment was carried out at the Arid Zone Research Centre, Dera Ismail Khan, in the 2017–18 growing season.to evaluate This influence regarding the application of rhizobacterial inoculants. Concerning soil properties, root and shoot structure, and wheat productivity. The study followed a randomized complete block design (RCBD) was implemented with five treatments, including a control and four bacterial inoculants: Enterobacter asburiae, Enterobacter mori, Pseudomonas aeruginosa, and Pseudomonas putida. These microbial strains were isolated from the rhizosphere of lentil plants. Crops, identified, as well as used for seed application of microbial inoculants. Various soil, development and productivity metrics were analyzed. These findings revealed that beneficial rhizobacteria (PGPR) had a notable impact on plant height as well as leaf length. Traits such as fresh and dry root weight, root surface area, root extent and root length concentration were notably affected as a result of the applied treatments. Among them, Enterobacter mori (T₂) led to the highest fresh and dry root weight and root area, while Pseudomonas putida (T₄) enhanced root length and root length density. Yield-related parameters, including thousand-grain weight, grain production, and straw output, were also substantially impacted. The maximum grain and straw productivity were recorded in the treatment with Enterobacter asburiae (T₁), whereas Pseudomonas aeruginosa (T₃) resulted in the maximum 1000-grain weight. Soil characteristics, including organic matter composition and overall nitrogen levels, and extractable phosphorus showed significant improvement in treatments inoculated with Pseudomonas putida (T₄) and Enterobacter mori (T₂), respectively. Overall, the results suggest that inoculation with Pseudomonas putida, Enterobacter asburiae, Enterobacter mori, and Pseudomonas aeruginosa improves soil nutrient content while enhancing wheat growth and productivity.
Keywords: Rhizobacteria; PGPR; Wheat; Biofertilizer